A CONCEPTUAL APPROACH TO THE SCIENTIFIC JUSTIFICATION OF THE MODIFICATION OF TECHNICAL MEANS AND TECHNOLOGICAL EQUIPMENT OF FOOD PRODUCTION - N. A. Yermoshin; Y. S. Romanchik (Современная наука и инновации)
The main directions and methods of developing technical solutions for improving the operational properties of food processing equipment are considered and analyzed. A conceptual approach to the scientific justification of technical solutions for the modification and development of technical devices using physical, mechanical, and chemical models of technological processes of food supply is proposed. The principles of modification of technical means of production and food qualimetry are revealed in the complex application of methods of taxonomy of functional characteristics and qualimetric indicators, analysis of accuracy and stability of technological processes, theory of experimental research, simulation modeling, as well as statistical methods.